2017
DOI: 10.1111/jzs.12169
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy of theRhinolophus macrotiscomplex (Chiroptera, Rhinolophidae) in Vietnam and nearby regions

Abstract: The taxonomic status of Rhinolophus macrotis sensu lato (s.l.) in Vietnam and adjacent territories remains problematic. To address this issue, we performed an integrated study of morphological, acoustic, and genetic characters of R. macrotis s.l.specimens and compared these with sympatric species within the philippinensis group (R. marshalli, R. paradoxolophus, and R. rex). Our results reveal that in addition to a cryptic species of R. macrotis previously found in Jiangxi and Jingmen, China, R. macrotis s.l. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…Natural history collections hold an invaluable resource of information on the world's biodiversity (Lister & Climate Change Research Group, 2011) and are indispensable for integrative taxonomic revisions (Goodman, Maminirina, Bradman, Christidis, & Appleton, 2010; Hassanin et al., 2017; Tu et al., 2017; Demos et al., 2019). Based on our experience, these collections can be considered reservoirs of hidden diversity (Fontaine, Perrard, & Bouchet, 2012), not necessarily restricted to cryptic species (Hebert, Penton, Burns, Janzen, & Hallwachs, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Natural history collections hold an invaluable resource of information on the world's biodiversity (Lister & Climate Change Research Group, 2011) and are indispensable for integrative taxonomic revisions (Goodman, Maminirina, Bradman, Christidis, & Appleton, 2010; Hassanin et al., 2017; Tu et al., 2017; Demos et al., 2019). Based on our experience, these collections can be considered reservoirs of hidden diversity (Fontaine, Perrard, & Bouchet, 2012), not necessarily restricted to cryptic species (Hebert, Penton, Burns, Janzen, & Hallwachs, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The barcode fragment of the CO1 gene (657 bp) was amplified and sequenced using the primers UTyr and C1L705 28 . PCR amplifications of the CO1 gene were performed as previously published 29 . PCR products were purified using ExoSAP Kit (GE Healthcare, UK) and sequenced using the Sanger method on an ABI 3730 automatic sequencer at the Centre National de Séquençage (Genoscope) in Evry (France).…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al (2016) used extensive sampling, phenotypic data, and multiple genetic markers to investigate the evolutionary history of R. episcopus and its sibling species, and revealed mito-nuclear discordance in these species. Tu et al (2017), Zhang et al (2018), and Liu et al (2019) performed integrative studies and demonstrated phenotypic and genetic divergence among R. episcopus and its closely related species, and revised their taxonomic status, which was debated for a long time (Liu et al, 2019;Sun & Feng, 2009;Sun et al, 2008Sun et al, , 2016Tu et al, 2017;Zhang et al, 2009Zhang et al, , 2018. Those studies revealed geographic variation in population genetic structure and acoustic characteristics within R. episcopus; however, the level of intraspecific differentiation and factors driving such differentiation are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…(2018), and Liu et al. (2019) performed integrative studies and demonstrated phenotypic and genetic divergence among R. episcopus and its closely related species, and revised their taxonomic status, which was debated for a long time (Liu et al., 2019; Sun & Feng, 2009; Sun et al., 2008, 2016; Tu et al., 2017; Zhang et al., 2009, 2018). Those studies revealed geographic variation in population genetic structure and acoustic characteristics within R. episcopus ; however, the level of intraspecific differentiation and factors driving such differentiation are still unclear.…”
Section: Introductionmentioning
confidence: 99%